The Experience Sampling Method ‐ a new digital tool for momentary symptom assessment in IBS: an exploratory study. Issue 9 (22nd June 2015) - Mujagic, Z.; Leue, C.; Vork, L.; Lousberg, R.; Jonkers, D. M. A. E.; Keszthelyi, D.; Hesselink, M. A.; van Schagen, T. J. C.; van Os, J.; Masclee, A. A. M.; Kruimel, J. W.
Abstract Background Retrospective questionnaires are frequently used for symptom assessment in irritable bowel syndrome (IBS) patients, but are influenced by recall bias and circumstantial and psychological factors. These limitations may be overcome by random, repeated, momentary assessment during the day, using electronic Experience Sampling Methodology (ESM). Therefore, we compared symptom assessment by ESM to retrospective paper questionnaires in IBS patients. Methods Twenty‐six IBS patients (Rome III) were included, of which 16 were diagnosed with panic disorder (DSM‐IV‐TR). Patients scored symptoms using end‐of‐day diaries during 14 days and the gastrointestinal symptom rating scale (GSRS) once. ESM was used on seven consecutive days during the same time period. Key Results End‐of‐day diary abdominal pain scores were 0.4 (SE 0.1, p < 0.001) point higher (on a 1‐to‐5‐point scale) compared to corresponding ESM mean‐scores in IBS patients. The difference was even more pronounced for upper abdominal pain scores assessed by the GSRS (4.77 ± 1.50) compared to ESM mean‐scores (2.44 ± 1.30, p < 0.001), both on 1‐to‐7‐point scale. For flatulence, comparable results were found. Nausea and belching scores showed small, but significant differences between end‐of‐day diary and ESM. All tested symptoms were scored higher on GSRS compared to ESM mean‐scores (p < 0.01). Affective comorbidity did not influence differences in pain reporting between methods. Conclusions & Inferences IBS patients report higher scores for abdominal pain in retrospective questionnaires compared to ESM, with a tendency to report peak rather than average pain scores. ESM can provide more insight in symptom course and potential triggers, and may lead to a better understanding of IBS symptomatology.